Analisis Efisiensi Saluran Tataniaga Biji Pinang Kering di Kecamatan Kuala Kabupaten Nagan Raya - Geta Ambartiasari; Rahmat Arfan (Formosa Journal of Sustainable Research, 2022)
The purpose of this study was to determine the pattern of commerce and efficiency of the business channel of dried betel nut in Kuala District, Nagan Raya Regency. Data were collected by conducting direct interviews with farmers, small collector traders (PPK), and large collector traders (PPB). Data analysis uses Structure, Conduct, and Performance approaches. The overall market structure in the betel nut business process in Kuala District tends to lead to a monopsony market structure. Seeing that the number of sellers and buyers is not balanced, the betel nut business system in Kuala District is inefficient, because it refers to the monopsony market structure. Of the three commercial channels, the most efficient commercial channel is channel I because it has the lowest margin value and the highest farmer's share so that from the farmer's side, the share of prices received by farmers is quite large.